Hungarian Monitoring, 18 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American presidential election campaign: portrait of George Bush - Polish strikes continue - Genscher's letter to Romanian foreign minister Domestic Affairs: - Presidential Council president welcomes apostolic nuncio Colasuono - Veszprém viaduct gets its name back - Fate of Transylvanian Hungarians - State Youth and Sports Office (ÁISH): sport leaders can also travel to Seoul Olympics at state's expense Külpolitika: - Amerikai választási kampány; George Bush portré - Folytatódnak a lengyel sztrájkok - Genscher levele a román külügyminiszterhez Belpolitika: - Az Elnöki Tanács elnöke fogadta Colasuono apostoli nunciust - Visszakapta a nevét a veszprémi viadukt - Az erdélyi magyarság sorsa - ÁISH: sportvezetők is utazhatnak a szöuli olimpiára állami pénzen